Fall armyworm responses to genetically modified maize expressing the toxin Cry 1A(b) - Mendes, Simone Martins; Boregas, Kátia Gisele Brasil; Lopes, Marcos Evangelista; Waquil, Matheus Soares; Waquil, José Magid (Pesquisa Agropecuaria Brasileira, 2011)
– The objective of this work was to evaluate biological parameters of maize fall armyworm (Spodoptera frugiperda) fed with Bt maize hybrids expressing the Cry 1A(b) toxin, and with its isogenic non-Bt hybrids. The experiments were carried out in the laboratory of Embrapa Milho e Sorgo, Sete Lagoas, MG, Brazil. The parameters evaluated were: survival of larvae after 48 hours, survival of larval and preimaginal phases, larvae biomass at 14 days of age, pupae biomass, larval development period, and feeding non‑preference of first instar larvae. Larvae of S. frugiperda show less resistance in the first 48 hours of feeding and during the entire larval phase in most Bt maize hybrids, in comparison to non-Bt maize. The biomass of larvae and pupae developed in Bt maize was always smaller, and the larval and preimaginal period were longer. There was interaction between the Cry 1A(b) toxin and the genetic base of the transgenic hybrids regarding survival and larval biomass. Newly hatched S. frugiperda larvae show preference for feeding on non-Bt maize.